Extreme anomalies under El Niño and La Niña developing tendencies restrain subsequent severe typhoons in the western North Pacific - Fang, Rong; Chen, Shumin; Li, Weibiao; Zhou, Mingsen; Zhang, Aoqi; Chen, Yilun (Frontiers in Earth Science, 2022)
Forecasting typhoon features over a few upcoming months is necessary for planning disaster prevention and predicting the drought/flood situation. However, the current methods are more suitable for forecasting the interannual to interdecadal variation trends, or demand huge computing resources and are unsuitable for the operation of short-term climate forecast. To devise other effective approaches, the correlation between the Oceanic Niño Index (ONI) in January and the frequency of severe typhoons (STYs) during 1959–2018 was analyzed for the two scenarios when the ONI trend during the previous year was higher and lower than zero. The reason for this classification is that the air‒sea conditions were different when the oceanic phenomena developed towards an El Niño or La Niña phase during the previous year, and the results of these trends affect the subsequent features of atmospheric dynamic factors that are favorable for TC development (relative vorticity and vertical velocity). The extreme anomalies under both the increasing and decreasing tendencies of ONI in January typically retrained the growth of STYs, as the subsequent decreasing ocean heat anomaly of the previous year was accompanied by a negative vorticity anomaly and downward vertical velocity anomaly in the lower atmosphere, and vice versa. Results from the forecast test show that the accuracy of the new approach was acceptable and somewhat higher than that of the current methods. Thus, these results can assist in developing a practical approach for typhoon forecasts.